Fabrication of hollow denture technique for highly resorbed ridges for geriatric cases-A literature review - Deepa Balu; Ahila Singaravel Chidembaranathan; Muthukumar Balasubramaniam (Wolters Kluwer Medknow Publications, 2022)
The purpose of the review was to validate the different methods used for the fabrication of hollow denture that gives the better retention and stability in highly resorbed conditions. This study includes various literatures that provide different techniques involved during for fabrication process of hollow denture and also incorporation of the various different materials such as salt, sugar crystals, chocolate syrup, soap, and latest advances including the three-dimensional (3D) resins that are used as the spacer material in the fabrication of these dentures. The results show that all these different techniques using the different spacer material possess the similar results of 25% reduction in weight of the dental prosthesis. There are increased retention, stability, and comfort in condition of highly resorbed conditions with increased interocclusal distance that also prevents the muscle atrophy and fatigue in elderly individuals.